Design, Fabrication, and Characterization of an Indigenously Fabricated Prototype Transferred Arc Plasma Furnace - Mandal A.K.; Dishwar R.K.; Sinha O.P. (My University, 2025)
The extraction of metals like Al and Si from bottom ash having alumina and silica requires high temperature for their reduction. Only transferred arc plasma (TAP) furnace could meet this requirement. The TAP furnace was fabricated indigenously for performing experiments in laboratory based on the information available in the literature, related to the furnace design. The furnace was fully characterized for its smooth functioning by observing parameters like arc length, energy, and electrode consumption as well as the generation of sound level. It was found that the required temperature could be achieved by varying arc length, arc current, power rating as well as plasma gases. Arc length could be adjusted by varying power rating and changing voltage for required heat distribution above the melt. The accessories like the charge feeding system, gas purification and its flow system, gas exit system, the pouring system were worked satisfactorily. Sound level could be controlled by controlling arc current with the plasma gas. The thickness of lining was found sufficient to hold liquid metal either in graphite or magnesite crucible. Increased melt temperature (200 °C) and 10-dB lower sound level could be achieved by using nitrogen plasma as compared to the normal arc. But, hydrogen plasma produces more 100 °C melt temperature, and 5-dB sounds as compared to nitrogen plasma. Based on the results of the operational trial, it could be concluded that the TAP furnace was found to be a suitable tool for melting 2-kg iron and its various attachment were also found to be trouble-free operation. © 1973-2012 IEEE.